Wheat germ as natural coagulant for treatment of palm oil mill effluent (POME) - Daud, Nor Shazwani; Mohd. Ghazi, Tinia Idaty; Ahamad, Intan Salwani (World Academy of Research and Publication, 2014)
The potential of wheat germ as a natural coagulant for treatment of palm oil mill effluent (POME) was explored. A series of jar test was conducted for the determination of best extraction method for the wheat germ, optimum dosage and optimum pH. The reported parameters were turbidity, TSS, COD and colour. It was found that the wheat germ extracted with 1M NaCl solution (WG-1M) achieved the highest reduction of turbidity, TSS, COD and colour at 99.1%, 95.6%, 61.7% and 67.8% respectively. This was attained at optimum dosage of 12 000 mg/L and an optimum pH of 2. Results showed that the wheat germ can be regarded as a new potential natural coagulant for the treatment of POME.